Tonal Music Twelve Analytic Studies - Kresky, Jeffrey (Indiana University Press, 1977)
A frequent approach to musical analysis is to consider one term or concept at a time, illustrating it with fragments of several compositions. But the format of this original and lucidly written book features entire tonal compositions, one per chapter, analyzed on several levels simultaneously. The author builds up from very simple musical forms, skillfully leading the reader through a measure-by-measure, indeed often beat-by-beat or note-by-note, analysis. The pieces span the period from Corelli to Debussy and hence illus-trate both the flexibility and the historical development of the tonal system. A concluding essay projects this development into the twentieth century, with implications for the analysis of nontonal music. The music discussed in five of the twelve chapters is supplied; the rest of the compositions are standard works.